Assessment of Work-Related Hand Injuries at Hospital Serdang, Selangor - Abood Al-Husuny, Ameer Najah (2011)
Introduction: Work-Related Hand Injuries (WRHIs) contribute to a significant workload of all accidents received at the Emergency Departments. The aim of this study is to determine the proportion and severity WRHI cases and factors associated at Hospital Serdang. Methodology: A cross-sectional study design was used in this study. The study duration was from January 2009 to December 2010 and the data collection continued five months from January 2010 to June 2010. Categorical variables were presented as frequencies and percentages. Continuous variables were presented as means with their 95% confidence interval (CI) and standard deviation. The Pearson's chi-square test (x2) was used to determine the associations between categorical variables. Binary Logistic regression was done for multivariate analysis. A p-value of <0.05 was considered as statistically significant. Results: The results showed that out of 428 industrial accidents, 106 (24.7%) were WRHIs. Among those with WRHI, 46.2% of them had severe WRHI. The overall mean age of the respondents was 30.27 (± 8.71 SD) years. Majority (95.3%) was male and 76.4% of the respondents were aged between 18 and 35 years. Majority (81.1%) of the injuries occurred between Monday to Friday and machines were the source in 68.9% of the WRHIs. Majority (53.8%) of the respondents were involved in metal-machinery industry. The most common mechanism of the hand injury (48.1%) occurred when the hand was caught in the operating part of the machine. Open fracture occurred in 32.1% of the WRHIs. Majority (62.2%) of the respondents had finger’s injuries. There was significant association between severity of WRHI with locations of injury, mechanisms of injury, sources of injury, sectors of industry and workplace crowding (p < 0.05). Conclusion: Among all the industrial accidents seen at Serdang Hospital, 24.7% were WRHI, with 46.2% of those with WRHIs faced severe hand injuries. Mechanical machine and metal-machinery sector of industry were the strongest predictors to indicate severe WRHI. Respondent’s medical history and social habits had no affect on Severity of WRHI. Key words: WRHI, MHISS and Hospital Serdang.